2007
DOI: 10.1080/08910600701278722
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in the mucosal microenvironment: vasoactive intestinal peptide modulates the down-regulatory action ofLactobacillus rhamnosuson LPS-induced interleukin-8 production by intestinal epithelial cells

Abstract: Intestinal epithelial cells (IECs) act as a key point of initial contact with bacteria in the microenvironment of the intestinal tract. Interactions between IECs and bacteria lead to alterations in IEC activity, including modified cytokine secretion patterns, which may influence the mucosal immune response. IECs respond to lipopolysaccharide (LPS) from gramnegative bacteria by production of pro-inflammatory cytokines, including interleukin-8 (IL-8). Two strains of Lactobacillus rhamnosus , R0011 and R0049, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…We hypothesised that SCFAs may regulate secretion of IL-8, which has been reported to be produced by human normal IECs and adenocarcinoma derived cell line such as HT-29 cells (Daig et al, 2000;Kolios et al, 1996;Li et al, 2001;Yomogida et al, 2008). IL-8 acts as a chemoattractant of neutrophils to the site of inflammation leading to accumulation and infiltration of immune cells at the site of inflammation and may cause tissue damage (Schuerer-Maly et al, 1994;Wood et al, 2007). IL-8 has also been implicated in tumorigenesis, increasing the expression of IL-8 and/or its receptors may enhance tumour cell proliferation, promote angiogenesis and induce tumourassociated macrophages to release more growth factors leading to cancer cell invasion at the tumour site (Lee et al, 2013;Ning & Lenz 2012;Waugh & Wilson 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesised that SCFAs may regulate secretion of IL-8, which has been reported to be produced by human normal IECs and adenocarcinoma derived cell line such as HT-29 cells (Daig et al, 2000;Kolios et al, 1996;Li et al, 2001;Yomogida et al, 2008). IL-8 acts as a chemoattractant of neutrophils to the site of inflammation leading to accumulation and infiltration of immune cells at the site of inflammation and may cause tissue damage (Schuerer-Maly et al, 1994;Wood et al, 2007). IL-8 has also been implicated in tumorigenesis, increasing the expression of IL-8 and/or its receptors may enhance tumour cell proliferation, promote angiogenesis and induce tumourassociated macrophages to release more growth factors leading to cancer cell invasion at the tumour site (Lee et al, 2013;Ning & Lenz 2012;Waugh & Wilson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this hypothesis, we initially determined viability of cells and the toxicity effects of mixed SCFAs at physiological concentrations in the lumen of human colon (Cummings et al, 1987;Kiefer et al, 2006;Treem et al, 1994). Similar concentrations were therefore used in IEC stimulation (Wood et al, 2007). The presence of SCFAs improved the growth of T4056 cells likely due to the provision of energy source by SCFAs (Kiefer et al, 2006;Wachtershauser & Stein 2000;Matthews et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human HT-29 or KATO III (gastric adenocarcinoma cells) stimulated with lipopolysaccharide derived from Escherichia coli yield a strong pro-inflammatory response as characterised by increased levels of interleukin-8 (IL- Dupont et al, 2000;Pham et al, 2000;Van Calsteren et al, 2002;Provencher et al, 2003;Peant et al, 2005R-11 Botes et al, 2008R-011 Roy and Ward, 2004R0052 I-1722Possemiers et al, 2010K1 Podlesny et al, 2011K300 Atassi et al, 2006Rosell-52 Diop et al, 2008Lactobacillus acidophilus YS or RO-52 Easo et al, 2002 8) (Wood et al, 2007). In these cell systems, R0011 was able to significantly reduce the levels of IL-8.…”
Section: In Vitro Studies Pertaining To Potentially Probiotic Mechanimentioning
confidence: 99%
“…In these cell systems, R0011 was able to significantly reduce the levels of IL-8. This outcome suggested that high levels of induction of protein kinases render human intestinal epithelial cells refractory to the modulatory effects of the L. rhamnosus R0011 (Wood et al, 2007). VIP is known to induce protein kinase A and elevate cAMP.…”
Section: In Vitro Studies Pertaining To Potentially Probiotic Mechanimentioning
confidence: 99%